2022
DOI: 10.3389/fpsyt.2022.976217
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of co-occurrence of non-suicidal self-injury and suicide attempt: Implications for clinical intervention and future diagnosis

Abstract: BackgroundNon-suicidal self-injury (NSSI) and suicide attempt (SA) are risk behaviors that lead to physical injury and even death in individuals, and are a very powerful risk factor when both occur together, with individuals presenting with more severe psychological and behavioral problems. Due to the different demographic characteristics of different study subjects, an overall understanding of the incidence and occurrence of this co-occurrence is lacking to clarify the focus of clinical interventions and futu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 61 publications
1
7
0
1
Order By: Relevance
“…Recent studies have identified nonsuicidal self-injury (NSSI) as a highly significant risk factor for future fatal and non-fatal suicide attempts (5)(6)(7). People with mental disorders who also have suicidal ideation and NSSI are clearly a group at highest risk of attempting suicide.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified nonsuicidal self-injury (NSSI) as a highly significant risk factor for future fatal and non-fatal suicide attempts (5)(6)(7). People with mental disorders who also have suicidal ideation and NSSI are clearly a group at highest risk of attempting suicide.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents showing both NSSI and SI or suicidal behavior have become increasingly common in clinical practice. Recent meta-analysis reported that combined incidence of NSSI and suicide attempt co-occurrence was 9.6% [ 15 ]. Suicidal behavior and self-harm in children and adolescents were increased significantly during the COVID-19 pandemic [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…NSSI is associated with various poor outcomes, such as cognitive impairment, lack of interpersonal and familial relationships, and increased rates of mood disorders among adolescents and young adults [7, 8]. According to a systematic review, the combined incidence of NSSI and suicide attempt co-occurrence was 9.6% [9]. However, there has been controversy over whether NSSI and suicide attempts should be regarded as the same or different concepts.…”
Section: Introductionmentioning
confidence: 99%